Perbandingan Ekstraksi Nikel Non-Sulfida dengan Teknik Sulfidasi dalam Upaya Peningkatan Ekstraksi Nikel pada Crude di PT X - Muhamad Ismatulloh; Fahny Ardian; Gabriel Ricardo Ananda Putra (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
Improving the efficiency and selectivity of nickel extraction is essential to meet increasing industrial demands and reduce processing costs. This study aims to compare the effectiveness of non-sulfide and sulfidation methods for nickel extraction from crude nickel ore. The extraction processes were conducted using Electric Furnace Units 5, 6, 7, and 8, which operate under the Rotary Kiln-Electric Furnace (RKEF) technology. The results show that Furnaces 5 and 6, which applied the non-sulfide method, produced low-grade ferronickel. In contrast, Furnaces 7 and 8, where sulfur was added (sulfidation process), successfully formed nickel sulfide (Ni₃S₂). This comparison indicates that sulfur addition in the extraction process can enhance the formation of more specific nickel compounds. However, further evaluation is required to assess the efficiency and environmental impact of both methods.